Standar Operasional Prosedur: pilar utama dalam peningkatan pengendalian internal - Santi, Fitriana; Aljanah, Syifa; Setyawati, Dyah (Jurnal Ilmiah Bisnis dan Perpajakan (Bijak), 2024)
Internal control plays a crucial role in the success of an organization. One form of internal control is the presence or absence of Standard Operating Procedures (SOPs) within a company. Company X, a service provider business, often faces operational challenges, particularly with uncollectible receivables, resulting in inefficiencies. This is due to the company neglecting SOPs and not adhering to standard sales and purchasing procedures. The objective of this research is to provide a flowchart that simplifies task separation and control for the company. The research employs a qualitative method with a case study approach, and data is collected through interviews. The results indicate that the company benefits significantly from the flowchart, as it ensures proper task separation and assignment.